SIMULATION OF RECONFIGURATION SYSTEM USING MATLAB-SIMULINK ENVIRONMENT - Thanh, Ngo Ngoc; Quang, Nguyen Phung (Journal of Computer Science and Cybernetics, 2018)
Reconfiguration strategy is intended to minimize losses and increase efficiency of the photovoltaic (PV) system under non-homogeneous solar irradiation based on irradiance equalization. The reconfiguration system (RS) includes: irradiance equalization algorithms which is effective in the calculation to find optimal configuration; dynamic electrical scheme (DES) switching matrix which is controlled to obtain the optimal configuration for PV array. The recent publications focus on bringing out the algorithms with the aim to select the optimal connection configuration and control DES switching matrix. However, no published work has used Matlab-simulink to simulate RS operation. In this paper, the author uses the Matlab-simulink environment to simulate RS operation. Through results, the model demonstrates that with RS, the effectiveness of the PV array performance can rise by 10-50% under non-homogeneous solar irradiation.